HOUSEHOLD, INSTITUTIONAL, AND COMMUNITY DETERMINANTS ASSOCIATED WITH DENGUE PREVENTION PREPAREDNESS - Anisa A. Jamito; Randy Ian F. Gallego; Shiennah L. Jamesula (Journal of Vocational Nursing, 2026)
Introduction: Dengue fever remains a persistent public health concern in the Philippines, considering the latest statistical data on recurrent outbreaks despite the present sustained efforts of various health agencies. It is therefore crucial to understand household-level preparedness and its associated sociobehavioral determinants to evaluate dengue prevention efforts in high-risk communities. Methods: This study employed a cross-sectional descriptive-correlational design among 125 household representatives in Barangay Singao, Kidapawan City, Philippines, using total enumeration sampling. Data were collected using a validated and reliable researcher-developed questionnaire (CVR = 0.7–0.9; Cronbach’s alpha = 0.85). In this study, household, institutional, and community determinants, which included household-level preventive capacity, local government health response, and community engagement, were examined in relation to dengue prevention preparedness across three domains: mosquito habitat management, mosquito bite prevention, and dengue transmission management. Descriptive statistics and Pearson's chi-square tests were utilized in the data analysis. Results: Households demonstrated generally high levels of dengue prevention preparedness across all three domains, particularly in mosquito habitat management and dengue transmission management. Household-level preventive capacity showed significant associations with all preparedness domains (p < 0.001). The prevention of mosquito bites (p = 0.032) and the control of dengue transmission (p = 0.010) were substantially correlated with local government health response, except for mosquito habitat management. Only mosquito habitat management was substantially correlated with community engagement (p = 0.047). Conclusions: The findings of this study indicate that household-level preventive capacity is consistently associated with dengue prevention preparedness, while institutional and community determinants show domain-specific and limited associations.